Physical and chemical characteristics of genipap fruit - Figueiredo, Raimundo W. de; Maia, Geraldo A.; Holanda, Luciano Flávio F. de; Monteiro, José Carlos S. (Pesquisa Agropecuaria Brasileira, 2014)
In this work, fruits from genipap (Genipa americana, L.) collected at the Maranguape county, CE, Brazil, were used. Physical measurements were made on ripe fruits to evaluate their industrial yield. Chemical and physical determinations were made on the homogenized pulp of the fruits in order to know their chemical composition. Liquid gas chromatography was used to evaluate the percentage of oil in the seed and pulp and the percentage of fatty acids presented in the lipid fraction of the seed and pulp oil was determined.